An Energetic N‐Oxide and N‐Amino Heterocycle and its Transformation to 1, 2, 3, 4‐Tetrazine‐1‐oxide. Issue 4 (17th November 2014) - Piercey, Davin G.; Chavez, David E.; Heimsch, Stefanie; Kirst, Christin; Klapötke, Thomas M.; Stierstorfer, Jörg
Abstract This study reports the preparation of 1‐amino‐1, 2, 3‐triazole‐3‐oxide (DPX2) and its transformation to 1, 2, 3, 4‐tetrazine‐1‐oxide. DPX‐2 provides insight into a novel N‐oxide/N‐amino high‐nitrogen system, being the first energetic material in this class. The ability of this material to undergo a nitrene insertion forming 1, 2, 3, 4‐tetrazine‐1‐oxide was also studied, and evidence for this material, the first non‐benzoannulated 1, 2, 3, 4‐tetrazine‐1‐oxide, is presented. The existence of both of these materials opens new strategies in energetic materials design. DPX2 was characterized chemically (Infrared, Raman, NMR, X‐ray) and as a high explosive in terms of energetic performances (detonation velocity, pressure, etc.) and sensitivities (impact, friction, electrostatic). DPX‐2 was found to possess good thermal stability and moderate sensitivities, indicating the viability of N‐amino N‐oxides as a strategy for the preparation of new energetic materials.